Production of Glycopeptide Derivatives for Exploring Substrate Specificity of Human OGA Toward Sugar Moiety - Li, Shanshan; Wang, Jiajia; Zang, Lanlan; Zhu, Hailiang; Guo, Jianshuang; Zhang, Jiabin; Wen, Liuqing; Chen, Yi; Li, Yanhong; Chen, Xi; Wang, Peng George; Li, Jing (Frontiers in Chemistry, 2019)
O-GlcNAcase (OGA) is the only enzyme responsible for removing N-acetyl glucosamine (GlcNAc) attached to serine and threonine residues on proteins. This enzyme plays a key role in O-GlcNAc metabolism. However, the structural features of the sugar moiety recognized by human OGA (hOGA) remain unclear. In this study, a set of glycopeptides with modifications on the GlcNAc residue were prepared in a recombinant full-length human OGT-catalyzed reaction using chemoenzymatically synthesized UDP-GlcNAc derivatives. The resulting glycopeptides were used to evaluate the substrate specificity of hOGA towards the sugar moiety, we anticipate this study will provide insight into the exploration of probes for O-GlcNAc modification as well as better understanding the roles of O-GlcNAc in cellular physiology.